Successful management of a case of true radicular dens invaginatus using platelet‐rich fibrin and guided tissue regeneration. (16th October 2019) - Mohan, Aparna; Krishnan, Unni; Akber, Mohammed; Nair, Mali G.; Balan, Anita
Abstract: A radicular variant of dens invaginatus (DI) is a rare form of dens invaginatus which develops in the root of the tooth after the crown development is completed. This report involves successful management of a case with guided tissue regeneration and describes the cone beam computed tomography (CBCT) characteristics of true radicular DI. A 20‐year‐old woman reported with recurrent swelling and pus discharge associated with her maxillary left central incisor (#21). Cone beam computed tomography (CBCT) of the region revealed #21 had an invagination in the mesial aspect of the coronal third of the root with a para radicular low‐density region perforating both the cortices. A diagnosis of true radicular variant of DI was made by exclusion. The case was managed with Biodentine ®, platelet‐rich fibrin and freeze‐dried demineralised bone graft. A 2‐year review showed that the tooth was functional with normal periodontal parameters and normal response to electric pulp sensibility test.